Vegetasi Kunci Habitat Anoa di Cagar Alam Pangi Binangga, Sulawesi Tengah (Jurnal Penelitian Kehutanan Wallacea, 2012)
Anoa is a wildlife species highly sensitive and selective to the habitat preferences. The study aims to identify the anoa habitat condition in the Nature Reserve of Pangi Binangga, environmental factors which determine the habitat of anoa, including other types of key vegetation of anoa habitats. The research method used is purposive sampling. Sample is determined by observation the track. Habitat of anoa is found such as footprints, skeleton and faeces that located on the highland, flat-sloping, near to the river, mild temperature on moist and acid soils. The density of trees, poles, sapling, seedlings and herbs respectively 302, 430, 1280, and 53250 inviduals/ha. Stratification of vegetation canopy consists of stratum B, C, D and E. The average of stand bassal area is 43.10 m2/ha. Habitat of anoa in Pangi Binangga Nature Reserve are dominated by tree species of Planchonella firms, Castanopsis acuminatissima, Platea sp., Magnolia liliifera, Palaquium quercifolium. The key indicator plants of anoa habitat are Alpinia sp, Diplazium esculentum (Rezt.) Sw. and Pinanga caesia.
Keywords: Anoa; Bubalus depressicornis; Bubalus quarlesi; habitat; Pangi Binangga Nature Reserve